Review: The impact of climate change awareness on children's mental well‐being and negative emotions – a scoping review. Issue 1 (6th December 2021) - Martin, Gina; Reilly, Kristen; Everitt, Haley; Gilliland, Jason A.
Abstract : Background: Climate change is a threat to children's physical health, but there are also implications for mental well‐being. Additionally, children may experience negative emotional responses stemming from an overarching awareness of the imminent threats to the planet due to climate change. Method: Using a scoping review, we examined the impact of climate change awareness on children's mental well‐being and negative emotions. Our aim was to identify and describe the existing literature and highlight priorities for future research. Three specific objectives guided the review: (1) to identify and provide an overview of research regarding the impact of climate change awareness on children's mental well‐being and negative emotions; (2) to summarize and clarify the terminology related to climate change awareness and children's mental well‐being and negative emotions; and (3) to make recommendations for areas of future research. Results: Thirty‐three articles were included in a narrative synthesis. Many articles were reviews or editorials/commentaries. Of the empirical research, most were from Europe, North America, and Australia. The articles emphasized a large range of negative emotions that children felt about climate change, with anxiety and worry being the most researched and discussed. Conclusions: The research on the impact of awareness of climate change on children's mental well‐being and negative emotions is in its early phases. Efforts are needed to advance conceptual clarity and operationalize concepts. Additionally, there is a need for research into the impact of climate change awareness on children's mental well‐being and negative emotions among a greater diversity of people and places. Existing studies provide an encouraging basis from which to develop future research.